Neurological Complications of Endocarditis: A Multidisciplinary Review with Focus on Surgical Decision Making - Carneiro, Thiago Santos; Awtry, Eric; Dobrilovic, Nikola; Fagan, Maura A.; Kimmel, Simeon; Weinstein, Zoe M.; Cervantes-Arslanian, Anna M. (Seminars in Neurology, 2019)
Infective endocarditis (IE) is a systemic disease with many potential neurologic manifestations including ischemic and hemorrhagic strokes, cerebral microbleeding, infectious intracranial aneurysms, meningitis, brain abscesses, and encephalopathy. The majority of left-sided (heart) IE patients have brain lesions that may alter management decisions, warranting the systematic use of magnetic resonance imaging. Many patients require surgical treatment of valvular disease, and central nervous system lesions weigh into decision making. Data regarding the timing of surgery are conflicting, but earlier surgery appears to be safe in most ischemic strokes, while ideally surgery should be delayed for 3 to 4 weeks in patients with hemorrhagic strokes. IE requires a multidisciplinary team to collaboratively care for the patient. In this article, we review the current understanding and management of the neurological complications of IE and their impact on the performance and timing of cardiac surgery.
Keywords: infectious endocarditis; infectious intracranial aneurysms; valvular surgery